PENGARUH KARAKTERISTIK PESAN KAMPANYE KESEHATAN TERHADAP SIKAP HIDUP SEHAT IBU IBU ANGGOTA POSYANDUDI KOTA BANDAR LAMPUNG - Basri, Hasan (Jurnal Bisnis Darmajaya, 2016)
Design of characteristic messagehave an effect on changing the public attitudes if to be done according to their trust. Target and main theme of campaign present the characteristic message whichis adapted by the trust of public receiver. This research analyze the characteristic message in environmental health campaign to create healthy life attitude as influence of expected campaign, namely persuationto specific public : the Posyandu Activators .This Research is based on the perspective of receiver, namely have focus at the influence of healthy life attitude. The methodologies applied are quantitative approach that are supported by qualitative data. The characteristic message is designed by The Office of Public Health Service (DinasKesehatan ) Kota Bandar Lampung. Hypothesis Test use the path analisys of 283 respondentas research sample. Result of research indicate that the characteristic message have influences to the healthy life attitude of Posyandu Activators .Keywords : Characteristic Message Campaign, Healthy Life Attitude